2017
DOI: 10.13042/bordon.2018.52067
|View full text |Cite
|
Sign up to set email alerts
|

El Profesorado Ante El Cyberbullying: Necesidades Formativas, Capacidad De Actuación Y Estrategias De Afrontamiento

Abstract: INTRODUCCIÓN. El cyberbullying ha despertado gran interés en la comunidad científica y educativa en la última década (Smith, 2016) por su preocupante asiduidad entre los escolares. Debido a la escasez de investigaciones que analizan la opinión del profesorado, este trabajo examina la percepción de docentes y equipos directivos sobre sus necesidades formativas, capacidad de actuación, propuestas de acción futuras en los centros, estrategias de afrontamiento y su relación con variables sociodemográficas. MÉTODO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Programs that will include components such as school and class atmosphere, social activities, cultivation of classroom relationships, and personal teacher-student relationships are necessary (Giménez-Gualdo & Carrión del Campo, 2018). The findings of the current study suggest specific variables that should be included in such programs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Programs that will include components such as school and class atmosphere, social activities, cultivation of classroom relationships, and personal teacher-student relationships are necessary (Giménez-Gualdo & Carrión del Campo, 2018). The findings of the current study suggest specific variables that should be included in such programs.…”
Section: Discussionmentioning
confidence: 92%
“…Researchers claim that despite some increase in awareness of CB, providing teachers with more specific programs for coping with CB is important in order to assist them with prevention and classroom intervention (Giménez-Gualdo & Carrión del Campo, 2018;Englander & Muldowney, 2007). Whereas most programs relate to identifying CB, its effects on students, and acquisition of tools for knowing how to manage CB incidents, many teachers report that their teacher training program did not properly prepare them for coping (Styron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that when encouraging students to report CB, programs should meaningfully involve a parent or guardian (Snakenborg et al, 2011), raise awareness of educational staff to the phenomenon of CB and its implications, teach educators how to recognize and cope with CB, and increase supervision of students using technology for learning purposes (Patchin & Hinduja, 2010). Researchers claim that despite some increase in awareness of CB, providing teachers with more specific programs for coping with CB is important in order to assist them with prevention and classroom intervention (Giménez-Gualdo & Carrión del Campo, 2018;Englander & Muldowney, 2007). Whereas most programs relate to identifying CB, its effects on students, and acquisition of tools for knowing how to manage CB incidents, many teachers report that their teacher training program did not properly prepare them for coping (Styron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating gender as it relates to teachers' awareness of CB have yielded contradictory findings. Some studies have found no gender differences (Huang & Chou, 2013); others have found women teachers have a higher chance of working with the perpetrator and soliciting help from others when needed (Bauman, Rigby, & Hoppa, 2008;Giménez-Gualdo & Carrión del Campo, 2018;Eden, Heiman, & Olenik-Shemsh, 2013). Huang and Chou (2013) claim that knowledge and skills regarding technology are more linked than gender to teachers' awareness.…”
Section: Factors Affecting Teachers' Intervention Strategiesmentioning
confidence: 99%
“…Mediante una pedagogía preventiva de la violencia basada en la formación de la personalidad del alumnado, a través de una acción pedagógica donde convivan muchos sistemas a la vez, a partir de la incorporación de modelos conductuales de aprendizaje humano y modelos cibernéticos aplicados a la instrucción escolar y, por último, a través de la transmisión de saberes y conocimientos ampliativos que no solo propaguen la convivencia sino nuestra capacidad humana de desarrollarla expansivamente (Martínez-Ferrer, et al, 2021). Así, para poder desarrollarlo es necesario dotar al profesorado de herramientas y habilidades específicas (Giménez & Carrión, 2018).…”
Section: Conclusionesunclassified